Implementasi Nilai-Nilai Pancasila di Sektor Perbankan - Bagas Darma Pradipta; Indah Pertiwi; Berti Wahyu Antari; Riska Andi Fitriono (Gema Keadilan, 2022)
In implementing the Basic Laws on Banking and the Basic Laws on Bank Indonesia, Pancasila values are needed in the banking sector in order to realize social justice in the form of equity. This study aims to make the Basic Banking Laws and Bank Indonesia Basic Laws applicable to the Indonesian banking industry so that they can reflect the values embodied in Pancasila and realize social justice in the banking sector.